2009
DOI: 10.1080/09637480902877998
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of antioxidant and anti-atherogenic properties ofGlycyrrhiza glabraroot usingin vitromodels

Abstract: The aim of present study was to evaluate antioxidant property of Glycyrrhiza glabra root extracts using in vitro models. The dose-dependent aqueous and ethanolic extracts demonstrated the scavenging activity against nitric oxide (concentration that caused 50% inhibition of nitric oxide radicals [IC(50)]=72 and 62.1 microg/ml, respectively), superoxide (IC(50)=64.2 and 38.4 microg/ml, respectively), hydroxyl (IC(50)=81.9 and 63 microg/ml, respectively), DPPH (IC(50)=43.6 and 28.3 microg/ml, respectively) and AB… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
41
1
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 76 publications
(46 citation statements)
references
References 31 publications
3
41
1
1
Order By: Relevance
“…Studies have reported that liquorice flavonoids have 100 times strong antioxidant activity when compared with antioxidant activity of vitamin E [24]. The aqueous and ethanolic extract of Glycyrrhiza glabra also shows dose dependent oxidative scavenging activity and have potential for protective effect against the human lipoprotein oxidative system [25]. In this reported study, antioxidant activity of aerial part and root of Glycyrrhiza glabra Linn.…”
Section: Therapeutic Potentials and Traditional Usesmentioning
confidence: 77%
“…Studies have reported that liquorice flavonoids have 100 times strong antioxidant activity when compared with antioxidant activity of vitamin E [24]. The aqueous and ethanolic extract of Glycyrrhiza glabra also shows dose dependent oxidative scavenging activity and have potential for protective effect against the human lipoprotein oxidative system [25]. In this reported study, antioxidant activity of aerial part and root of Glycyrrhiza glabra Linn.…”
Section: Therapeutic Potentials and Traditional Usesmentioning
confidence: 77%
“…Glycyrrhizin, the main sweet-tasting constituent of G. uralensis, has been reported to scavenge free radicals and block the chain reaction of lipid peroxidation (Binic et al, 2013). Moreover, its antioxidant, anti-inflammatory, chemopreventive, and antiproliferative activity have been reported (Rahman et al, 2007;Visavadiya et al, 2009;Binic et al, 2013).However, information on the cosmeceutical activity of G. uralensis is limited. G. uralensis extract in most research has been mainly prepared in methanol.…”
Section: Introductionmentioning
confidence: 99%
“…[15] G. glabra (Yeshtimadhu) contain phenolic component exhibit antioxidant activity. [16] Z. officinale (Sunthi) contains many antioxidants such as beta-carotene, ascorbic acid, terpenoids, alkaloids, and polyphenols such as flavonoids, flavones glycosides, and rutin. [17] B. arundinacea (Vamshalochana) contains phenolic compounds such as phenolic acids, flavonoids, and tannins which shows the antioxidant activity of the plant.…”
Section: Research Articlementioning
confidence: 99%